2012
DOI: 10.1136/bmj.e4800
|View full text |Cite
|
Sign up to set email alerts
|

Shift work and vascular events: systematic review and meta-analysis

Abstract: Objective To synthesise the association of shift work with major vascular events as reported in the literature.Data sources Systematic searches of major bibliographic databases, contact with experts in the field, and review of reference lists of primary articles, review papers, and guidelines.Study selection Observational studies that reported risk ratios for vascular morbidity, vascular mortality, or all cause mortality in relation to shift work were included; control groups could be non-shift ("day") workers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
532
2
17

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 670 publications
(566 citation statements)
references
References 62 publications
15
532
2
17
Order By: Relevance
“…A systematic review and meta-analysis by Vyas et al in 2012 of eleven prospective cohort studies, thirteen retrospective cohort studies and ten case-control studies showed convincing evidence that people working shifts have an approximately 20 % increased risk of myocardial infarction (risk ratios (RR) 1·23 (95 % CI 1·15, 1·31)), coronary events (RR 1·24 (95 % CI 1·10, 1·39)) and ischaemic stroke (RR 1·05 (95 % CI 1·01, 1·09)) (21) . Their analysis of unadjusted and adjusted RR both indicated similar results.…”
Section: Shift Workers Disease Risk and Dietary Patternsmentioning
confidence: 99%
“…A systematic review and meta-analysis by Vyas et al in 2012 of eleven prospective cohort studies, thirteen retrospective cohort studies and ten case-control studies showed convincing evidence that people working shifts have an approximately 20 % increased risk of myocardial infarction (risk ratios (RR) 1·23 (95 % CI 1·15, 1·31)), coronary events (RR 1·24 (95 % CI 1·10, 1·39)) and ischaemic stroke (RR 1·05 (95 % CI 1·01, 1·09)) (21) . Their analysis of unadjusted and adjusted RR both indicated similar results.…”
Section: Shift Workers Disease Risk and Dietary Patternsmentioning
confidence: 99%
“…As a consequence, most aspects of their physiology are orchestrated in a rhythmic way by the circadian clock (from the Latin circa diem, meaning "about a day"), an endogenous and autonomous oscillator with a period of around 24 h (1, 2). Not surprisingly, perturbations of this clock in mammals lead to pathologies including psychiatric, metabolic, and vascular disorders (1,3,4). At the organismal scale, the oscillatory clockwork is organized in a hierarchal manner.…”
mentioning
confidence: 99%
“…Shift workers are prone to obesity (5)(6)(7)(8)(9) and associated co-morbidities such as diabetes (5,6,8), high cholesterol (7-10), cardiovascular disease (5,6,11,12), gastrointestinal problems (5,6,13), and metabolic disturbances (5,6,(14)(15)(16). In addition, shift workers have an increased risk for coronary heart disease and stroke with mortality rates being highest among workers with the longest history of shift work (17)(18)(19)(20).…”
mentioning
confidence: 99%